Annotation of functional impact of voltage‐gated sodium channel mutations. Issue 5 (28th February 2017) - Hinard, Valérie; Britan, Aurore; Schaeffer, Mathieu; Zahn‐Zabal, Monique; Thomet, Urs; Rougier, Jean‐Sébastien; Bairoch, Amos; Abriel, Hugues; Gaudet, Pascale
Abstract : We present the Ion Channels Variants Portal, a corpus of variants of medical interest in the 9 human voltage‐gated sodium channel genes and their associated molecular and cellular phenotypic impact. The portal describes 672 variants in the 9 human VGSC genes each associated with at least one molecular or clinical observation, for a total of 4, 658 observations extracted from 264 different research articles. Abstract: Voltage‐gated sodium channels are pore‐forming transmembrane proteins that selectively allow sodium ions to flow across the plasma membrane according to the electro‐chemical gradient thus mediating the rising phase of action potentials in excitable cells and playing key roles in physiological processes such as neurotransmission, skeletal muscle contraction, heart rhythm, and pain sensation. Genetic variations in the nine human genes encoding these channels are known to cause a large range of diseases affecting the nervous and cardiac systems. Understanding the molecular effect of genetic variations is critical for elucidating the pathologic mechanisms of known variations and in predicting the effect of newly discovered ones. To this end, we have created a Web‐based tool, the Ion Channels Variants Portal, which compiles all variants characterized functionally in the human sodium channel genes. This portal describes 672 variants each associated with at least one molecular or clinical phenotypic impact, for a total of 4, 658 observations extracted from 264 different research articles. These data were captured as structured annotations using standardized vocabularies and ontologies, such as the Gene Ontology and the Ion Channel ElectroPhysiology Ontology. All these data are available to the scientific community via neXtProt athttps://www.nextprot.org/portals/navmut .